The Role of Investigators in Implementing Restorative Justice for the Crime of Beatings in Ujungberung, Bandung City - Rachman, Fitriana Sidikah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The criminal act of beatings still occurs every year in the jurisdiction of the Ujungberung police sector. The perpetrators of the crime of beatings were not only committed by adults, but also by children. So that children who are in conflict with the law do not continue to the criminal justice process, they require serious handling from investigators. Therefore, the urgency of research regarding the role of investigators in implementing Restorative Justice for criminal acts of beatings in the jurisdiction of the Ujungberung police sector is urgently needed. The aim of this research is to find out the role of obstacle mechanisms and investigators' efforts in implementing Restorative Justice for the crime of beatings. This research method uses descriptive analysis. The data sources used are primary data sources, namely data obtained directly from the Criminal Investigation Department of the Ujungberung police sector and secondary data sources obtained through books, police legal regulations, documents and internet media related to research. The results of the research are that investigators have a very important role in handling cases of criminal acts, especially those committed by children, by using another alternative, namely Restorative Justice, in resolving the problem of criminal acts of children so that the case is not forwarded to the criminal justice process.